Sensitive Label-Free Biomolecular Detection Using Thin Silicon Waveguides. (16th June 2008) - Densmore, A.; Xu, D.-X.; Janz, S.; Waldron, P.; Lapointe, J.; Mischki, T.; Lopinski, G.; Delâge, A.; Schmid, J. H.; Cheben, P.
Abstract : We review our work developing optical waveguide-based evanescent field sensors for the label-free, specific detection of biological molecules. Using high-index-contrast silicon photonic wire waveguides of submicrometer dimension, we demonstrate ultracompact and highly sensitive molecular sensors compatible with commercial spotting apparatus and microfluidic-based analyte delivery systems. We show that silicon photonic wire waveguides support optical modes with strong evanescent field at the waveguide surface, leading to strong interaction with surface bound molecules for sensitive response. Furthermore, we present new sensor geometries benefiting from the very small bend radii achievable with these high-index-contrast waveguides to extend the sensing path length, while maintaining compact size. We experimentally demonstrate the sensor performance by monitoring the adsorption of protein molecules on the waveguide surface and by tracking small refractive index changes of bulk solutions.